Ephippia production and genetic biodiversity in tropical cladoceran Moina micrura kurz - Osman, Mohd Azuraidi (2012)
In Malaysia, the imported Artemia nauplii is a standard larval diet in aquaculture and hatchery production system due to its availability in dormant form. However, this imported live feed is expensive and they can only survive for few hours in freshwater. Therefore, an easily available inexpensive local live-feed alternative for this imported species is desirable. In this study, the effect of different food concentrations and feeding frequencies on the production of ephippia had been investigated. Different food concentrations consisting of Nannochloropsis oculata (4x106 cells/ml, 4x104 cells/ml, 4x102 cells/ml, no food supply as control) and different feeding frequencies (3 days,3 and 5 days, 5 days, 8 days, 8 and 3 days and daily) were used. The highest mean number of ephippia (7.33±1.53 ephippia) was produced when the cultures were fed every 3 and 5 days alternately. When the cultures were fed with 4x10⁶ cells/ml, no ephippia was produced due to the high amount of food available. In another set of experiment, parthenogenetic reproduction,appearance of males and production of ephippia in M. micrura were studied. Two hundreds female individuals aged less than 24 hours were used. The cultures were fed with N. oculata at different food concentrations (4x106 cells/ml, 4x104 cells/ml, 4x102 cells/ml, no food supply as control) for 12 days. The highest number of males (186.7±23.1 males/l) was produced in the cultures fed with 4x102 cells/ml of N. oculata when population density reached > 1600 individuals/l. Similarly, the highest total mean number of ephippia (160.0±0.0 ephippia/l) was achieved with M. micrura fed with 4x102 cells/ml of N. oculata when the population density reached > 2000 individuals/l. Combination of limited food supply and high population density were needed to trigger the ephippia production. The hatchability of the ephippia that were produced in the earlier experiments was studied. In this experiment, only the ephippia containing resting eggs were used. Under the optimum environmental parameters (temperature 25±2°C, pH 5-9,photoperiod ≥8 hours light per day) none of the ephippia containing resting eggs hatched. These “weak eggs” might be caused by the maternal factor where the production ephippia is not normally occurs. The mechanism for hatching process is not well developed yet in this clone of M. micrura. In the earlier experiments, M. micrura reproduced by both asexual and sexual reproduction. Hence, genetic variation within asexual and sexual generation of M. micrura was investigated. Gene sequences of 16S rRNA mtDNA and Cytochrome C Oxidase Subunit 1 were used. Both genes show 100% similarity of the nucleotide sequences between different generations of asexual M. micrura. However, comparison of the 16S rRNA mtDNA gene sequences between asexual and sexual generations shows that the level of similarity between the sequences was only 55.80 to 56.82%, whereas Cytochrome C Oxidase Subunit 1 gene sequences shows 49.50 to 58.86% of similarity. This study clearly illustrated that production of ephippia in tropical M. micrura requires combination of low food availability and crowding condition. The failure of the eggs to hatch could be due to low synchronization of male production and ephippia formation in tropical M.micrura. The study also showed that sexual reproduction produces a new generation of M. micrura with higher genetic variation.